Réponse :
Bonjour
Exercice 2
on va utiliser ici l'identité remarquable : (a + b)(a - b) = a² - b²
A = (x - 2)(x + 2) = x² - 2² = x² - 4
B = (5 - y)(5 + y) = 5² - y² = 25 - y²
C = (3x + 5)(3x - 5) = (3x)² - 5² = 9x² - 25
D = (10 - 7z)(10 + 7z) = 10² - (7z)² = 100 - 49z²
Exercice 3
On va utiliser la même identité remarquable, mais dans l'autre sens :
a² - b² = (a + b)(a - b)
A = x² - 16 = x² - 4² = (x + 4)(x - 4)
B = 1 - y² = 1² - y² = (1 + y)(1 - y)
C = 100x² - 7 = (10x)² - (√7)² = (10x + √7)(10x - √7)
D = 36 - 81z² = 6² - (9z)² = (6 + 9z)(6 - 9z)